A Felvidék és a Dél-Dunántúl gazdasági és társadalmi kapcsolatai a 18-19. században - Kaposi, Zoltán (Közép-Európai Közlemények, 2011)
In my study I examine the social and economical relations of two regions which are far from each other: South Transdanubia and Upper Hungary. Significant amount of population migrated from North Hungary to the southern regions in the 18th century. Every social group was involved in this migration from the nobility to serfs. I analyse the consequences of this relocation in the next two hundred years through the pattern of the Országh-family (came from Trencsén shire, Upper Hungary). As a result of the relocation, kinship relations were not torn, instead, many other noble families moved to Somogy and Baranya shires. This dozen of families were fitting in the south landowner’s social layer in a long time. This social adaptation was going off in four dominant ways. Most of them chose the magisterial and officer occupations, but those who held clerical, military and farmer positions were also successful. From the study of the case I derive the conclusion that the inland migration of the nobility contributed to the unifying process of the society.